Website to help farmers bargain better - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Website to help farmers bargain better, Economic Times of India, 31 May 2002 It´s a well-known fact that Indian farmers rarely know the actual price and stock level of his produce at the mandis where they come to sell it.